2016
DOI: 10.1016/j.scriptamat.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

In search of amorphization-resistant boron carbide

Abstract: 2016-11-03T14:11:40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 47 publications
(91 reference statements)
3
37
0
1
Order By: Relevance
“…As a ceramic, the compressive strength of boron carbide is significantly higher than its tensile strength, and so even though the overall pressure in the region appears to be compressive, localized circumferential tension may exist along the boundary of the expanded amorphized region. This circumferential tensile stress may explain observations of cracks initiating from amorphized bands as well as the link between amorphization and comminution …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…As a ceramic, the compressive strength of boron carbide is significantly higher than its tensile strength, and so even though the overall pressure in the region appears to be compressive, localized circumferential tension may exist along the boundary of the expanded amorphized region. This circumferential tensile stress may explain observations of cracks initiating from amorphized bands as well as the link between amorphization and comminution …”
Section: Resultsmentioning
confidence: 92%
“…(A) TEM images show amorphized regions of various sizes and shapes near the tip of an indentation on boron carbide. (B) Amorphized islands appear close to the indentation . (C) Lattice rotations formed about an amorphized island and (D) a dislocation along one of the long, thin amorphized bands [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include operation at ultrahigh pressures or contact loads (10 GPa‐1 TPa), such as those generated within diamond anvil cells (DACs), machining tools (eg, cutting, drilling, grinding) which benefit from super‐ and ultrahard materials, and operation under highly dynamic loads found, for example, in armor applications, where impact pressures can exceed 10 GPa . While phase transformations under pressure can lead to the discovery of new structures with novel properties, they may also be deleterious to the expected performance, as in the solid‐state amorphization of B 4 C under high‐velocity impacts . As is the case with ballistic armor, the discovery and fundamental understanding of superhard materials is still in its early stages of identifying and leveraging advanced simulation, synthesis, and characterization tools.…”
Section: Ceramics For Extreme Environmentsmentioning
confidence: 99%
“…B 4 C consists of 12‐atom icosahedra (mostly B 11 C) connected via 3‐atom linear chains (eg, ‐CBC‐). Subhash et al suggested that doping Si, Ni and B into boron carbide could prevent the icosahedra from collapsing, thus mitigating amorphization in boron carbide. An et al performed density functional theory calculations and proposed that replacing ‐CBC‐ chain with Si–Si chain (Si‐doping) would stabilize the icosahedra, so that the system could shear without breaking the icosahedra and alleviating amorphization .…”
Section: Introductionmentioning
confidence: 99%